2021
DOI: 10.1007/s10551-020-04706-y
|View full text |Cite
|
Sign up to set email alerts
|

Quaker Business Ethics as MacIntyrean Tradition

Abstract: This paper argues that Quaker business ethics can be understood as a MacIntyrean tradition. To do so, it draws on three key MacIntyrean concepts: community, compartmentalisation, and the critique of management. The emphasis in Quaker business ethics on finding unity, as well as the emphasis that Quaker businesses have placed on serving their local areas, accords with MacIntyre’s claim that small-scale community is essential to human flourishing. The emphasis on integrity in Quaker business ethics means practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…Our study has a number of theoretical and practical implications for business ethics scholarship. While our study deepens an understanding of subjectivity and normativity in meaningful work in the Buddhist and Quaker contexts, various scholars have suggested that various spiritual or religious domains can be conceptualized as 'traditions' in the MacIntryian sense (Burton & Sinnicks, 2021). There are also a number of traditions in the much broader sense: Buddhism, Marxism, and even Liberalism, for example.…”
Section: Conclusion and Avenues For Future Studiesmentioning
confidence: 70%
See 2 more Smart Citations
“…Our study has a number of theoretical and practical implications for business ethics scholarship. While our study deepens an understanding of subjectivity and normativity in meaningful work in the Buddhist and Quaker contexts, various scholars have suggested that various spiritual or religious domains can be conceptualized as 'traditions' in the MacIntryian sense (Burton & Sinnicks, 2021). There are also a number of traditions in the much broader sense: Buddhism, Marxism, and even Liberalism, for example.…”
Section: Conclusion and Avenues For Future Studiesmentioning
confidence: 70%
“…Quaker participants tried to resist the kind of severe moral compartmentalization described by MacIntyre (1999MacIntyre ( , 2008. As Burton and Sinnicks (2021) noted, compartmentalization of the self is especially likely to arise in the context of work and leaves an individual unable to adjudicate between competing organizational and spiritual or normative demands. In the Quaker tradition, the theological idea of unity with God and an emphasis on continuity between the spiritual and social life was central to their conception of morality and enabled Quakers to move moral purpose beyond the contextspecificity of a situation and avoid "cross-context application of the virtues" (p. 7) in order that 'right' action is more easily discerned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recent research has demonstrated however, employees who understand themselves as participants in a tradition account for their 'calling' in terms provided by the rationality internal to that tradition e.g. Buddhist managers (Burton & Vu, 2020) and Quaker businesses (Burton & Sinnicks, 2021), whereas for the expressivist, deeply felt meaning is the only ground for such a claim. These conceptualizations cannot but be in radical tension with one another.…”
Section: Introductionmentioning
confidence: 99%
“…A sense of spirituality encompasses an inwardness in evaluating one's own moral and ethical behavior based upon the philosophy, teachings, principles, and commitments of a particular spiritual tradition. Spiritual practice, therefore, embeds normative and traditioned content, and yet allows space for individual interpretation and personal experience, and accords with the idea of life as a spiritual journey, a path, and spiritual progress (Burton & Sinnicks, 2021;, which contrasts with the commitments of religion that foreground objective super-naturalist accounts that rely upon the existence of an ultimate God (Michaelson, 2019). Spiritual practice is a way in which practitioners develop moral and normative judgements when they encounter various contradictory situations in CSR, and provides a context within which to examine our research question-how do spiritual practitioners use their spiritual tradition to morally manage and justify tensions associated with CSR within organizations?…”
Section: Introductionmentioning
confidence: 99%